2021
DOI: 10.1108/compel-08-2020-0286
|View full text |Cite
|
Sign up to set email alerts
|

Simple use of the Maclaurin series method for linear and non-linear differential equations arising in circuit analysis

Abstract: Purpose The purpose of this paper is to investigate the circuit analysis differential equations, which play an important role in the field of electrical and electronic engineering, and it was necessary to propose a very simple and direct method to obtain approximate solutions for the linear or non-linear differential equations, which should be simple for engineers to understand. Design/methodology/approach This paper introduces a simple novel Maclaurin series method (MSM) to propose an approximate novel solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, most economic systems have long-term memories. Therefore, the impact of memory effect on the dynamics of our model by using the new generalized Hattaf fractional (GHF) derivative [7,8] and other fractal-fractional derivatives as used in [4,15,16], will be the main purpose of our future works.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most economic systems have long-term memories. Therefore, the impact of memory effect on the dynamics of our model by using the new generalized Hattaf fractional (GHF) derivative [7,8] and other fractal-fractional derivatives as used in [4,15,16], will be the main purpose of our future works.…”
Section: Discussionmentioning
confidence: 99%
“…The mild conditions assumed to conduct our study permit applying our theoretical results to a wide variety of real-world scenarios where probability distributions must be inferred from all the model data. Our study can be extended to other problems in Physics formulated by means of generalizable differential equations with uncertainties as well as to study the randomized versions of recent techniques that have demonstrated to be very useful to deal with linear and nonlinear problems in Physics [24] and [25].…”
Section: Discussionmentioning
confidence: 99%
“…The one-dimensional non-homogeneous partial differential equations with a variable coefficient are solved by using homotopy perturbation method and Laplace transformation [24]. Linear and non-linear differential equations arising in circuit analysis are investigated by using Maclaurin series method [25]. The analysis of Caputo fractional-order dynamics of Middle East Lungs Coronavirus (MERS-CoV) model are discussed in [26].…”
Section: Introductionmentioning
confidence: 99%